2016
DOI: 10.1113/jp271690
|View full text |Cite
|
Sign up to set email alerts
|

Kainate receptor pore‐forming and auxiliary subunits regulate channel block by a novel mechanism

Abstract: Key points Kainate receptor heteromerization and auxiliary subunits, Neto1 and Neto2, attenuate polyamine ion‐channel block by facilitating blocker permeation.Relief of polyamine block in GluK2/GluK5 heteromers results from a key proline residue that produces architectural changes in the channel pore α‐helical region.Auxiliary subunits exert an additive effect to heteromerization, and thus relief of polyamine block is due to a different mechanism.Our findings have broad implications for work on polyamine block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 72 publications
(158 reference statements)
2
58
0
Order By: Relevance
“…A similar mechanism also accounts for the relief of block in GluK2/GluK5 KAR heteromers ( Brown et al, 2016 ), suggesting that multiple structural pathways can affect channel block and permeation. Importantly, under both conditions, blocker permeation occurs at more negative and physiologically relevant membrane potentials ( Brown et al, 2016 ). The AMPAR auxiliary proteins stargazin (γ2) and cornichon-3 (CNIH-3) also attenuate polyamine block ( Soto et al, 2007 ; Coombs et al, 2012 ), but the underlying mechanism has yet to be determined.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…A similar mechanism also accounts for the relief of block in GluK2/GluK5 KAR heteromers ( Brown et al, 2016 ), suggesting that multiple structural pathways can affect channel block and permeation. Importantly, under both conditions, blocker permeation occurs at more negative and physiologically relevant membrane potentials ( Brown et al, 2016 ). The AMPAR auxiliary proteins stargazin (γ2) and cornichon-3 (CNIH-3) also attenuate polyamine block ( Soto et al, 2007 ; Coombs et al, 2012 ), but the underlying mechanism has yet to be determined.…”
Section: Introductionmentioning
confidence: 89%
“…However, appreciating that auxiliary proteins attenuate channel block in AMPARs and KARs ( Jackson and Nicoll, 2011 ), the potential contribution of blocker permeation to the overall block mechanism has recently been evaluated. For example, a study of homomeric GluK2 KARs revealed that auxiliary proteins Neto1 and Neto2 relieve polyamine channel block by enhancing blocker permeation rates ( Brown et al, 2016 ). A similar mechanism also accounts for the relief of block in GluK2/GluK5 KAR heteromers ( Brown et al, 2016 ), suggesting that multiple structural pathways can affect channel block and permeation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Neto1/Neto2 have emerged as auxiliary KAR subunits capable of regulating almost every parameter of receptor function (Copits and Swanson, 2012; Howe, 2015). Overexpression studies in heterologous cells or neurons have demonstrated that Netos regulate KAR desensitization and deactivation kinetics, channel open probability, ligand affinity, ion permeation, and subcellular localization (Brown et al, 2016; Copits et al, 2011; Fisher, 2015; Fisher and Mott, 2012, 2013; Griffith and Swanson, 2015; Orav et al, 2017; Palacios-Filardo et al, 2016; Zhang et al, 2014; Zhang et al, 2009). Consistent with these findings, studies at hippocampal mossy fiber to CA3 pyramidal cell (MF-CA3) synapses indicate that Neto1 regulates binding affinity, kinetics, and synaptic targeting of native GluK2/3-containing postsynaptic KARs (Straub et al, 2011a; Tang et al, 2011; Wyeth et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the researchers observed that the KAR auxiliary proteins Neto1 and Neto2 relieve polyamine block by making it easier for polyamines to pass through the ion channel (5). Because AMPARs and KARs are closely related, Brown says, “it totally made sense to ask whether this could also be happening with AMPA receptors.”…”
mentioning
confidence: 99%